«BRAT» Crowned Collins Dictionary 2024 Word of the Year – new Word or Cultural Phenomenon - Kruhlij, Olena R. (Волинський національний університет імені Лесі Українки, 2024)
The term «brat» has evolved into a cultural phenomenon, transcending its traditional use to describe a misbehaving child. While the word has roots that date back centuries, its contemporary usage has transformed it into a symbol of confidence, independence, and a hedonistic lifestyle particularly within youth culture. Pop culture, social media, and the broader societal embrace of self-expression, rebellion, and unapologetic living have notably influenced such a cultural shift.
Keywords: new word; cultural phenomenon; dictionary